Application of Virtual Laboratory assisted Discovery Learning Model to Improve Science Process Skills and Learning Outcomes in Circulatory System Material - Misbahul Jannah; Ibnu Khaldun; Safrida Safrida (Postgraduate, University of Mataram, 2021)
Discovery learning (DL) model is a learning model that hones students' process skills in finding concepts. Science process skills are needed to support optimal learning outcomes. The absence of a laboratory is thought to be the cause of the less optimal learning process so that supporting media such as virtual laboratories (VL) are needed. This study aims to determine the effect of implementing the VL-assisted DL model to improve Science Process Skills (SPS) and student learning outcomes in the circulatory system material. The research design used was the pretest-posttest control group design. The study population was all students of class VIII Junior High School Darul Ihsan Aceh Besar, and the sample selection was using random sampling techniques so that 60 students were selected as the research sample who were divided into two classes. The results showed that the application of the VL-assisted DL model in the experimental class experienced an increase in SPS by 71.05 (high category) compared to the control class. The application of the VL-assisted DL model also experienced an increase in learning outcomes, namely 73.16 (high category). The conclusion in this study is the application of the VL-assisted DL model to the circulatory system material has an effect on improving SPS and learning outcomes